Innovative oral spray-dried Idebenone systems to improve patient compliance. (2nd July 2016) - Lauro, M. R.; Carbone, C.; Sansone, F.; Ruozi, B.; Chillemi, R.; Sciuto, S.; Aquino, R. P.; Puglisi, G.
Abstract: Idebenone is a high permeable drug with very slight water solubility that affects the dissolution rate in the biological fluids, causing an irregular and limited in vivo absorption after oral administration. Moreover, it is marketed in Europe as tablets equivalent to 150 mg, with the consequent administration of multiple dose of solid unit to obtain the correct dose, a deterrent for the patients' compliance. According to these considerations, our goal was to develop spray-dried microparticles using a soluble β-cyclodextrin (CD) polymer and an enhancer of dissolution rate, such as carboxymethyl cellulose, to obtain a formulation easily dosable and soluble in water. The complex in solution was evaluated by phase solubility studies and the Idebenone/CD molar ratio selected was 1:1. According to Higuchi and Connors, adding carboxymethyl cellulose, a Bs-type profile was obtained. This result was due to the presence of carboxymethyl cellulose that competes with the CD in forming Idebenone microsystems, reducing of 10-fold the formulation bulk. UV–Vis absorption, 1 H nuclear magnetic resonance and circular dichroism showed the formation of the CD/Idebenone inclusion complex conﬁrmed also by differential scanning calorimetry, Fourier transform infrared spectroscopy and fluorescence microscope (FM). The water solubility data and the in vitro dissolution tests performed in simulated gastric fluid, showed an increase of the drug water interaction due to the presence of the CD and carboxymethyl cellulose, both able to improve drug wettability, water solubility and dissolution rate. This approach seems to be suitable to produce microsystems which are able to enhance the in vivo absorption of Idebenone after oral administration and to increase the patient compliance.